Arthropods assiciated with the stinging nettle in Hungary - Bozsik, András (Acta Agraria Debreceniensis, 2011)
Stinging nettle (Urtica dioica Linnaeus) (Urticaceae) is a well known medicinal plant cultivated in some European countries for a long time. Because of its multiple usability (food, medicinal plant, feed, fiber), adventageous agrotechnical qualities and low demands for plant protection, its more extensiv utilization can be expected. However, during cultivation from time to time little damages can be occurred on it. The aim of this paper is to show and estimate the most important arthropods (pests and natural enemies) of stinging nettle. Under the pests characterized in the paper according to the references the peacock and the small tortoiseshell are the most important species living on stinging nettle. Their individuals from time to time propagated can cause an important damage on nettle leaves in cultivated nettle stands or assemblages. On the base of a 12 year observation period (Gödöllő, Debrecen, 1998-2010) the following species have been observed: Psylliodes attenuata, Chrysomela fastuosa, Phyllobius pomaceus, Pleuroptya ruralis, Inachis io, Aglais urticae, Microlophium evansi, Microlophium carnosum, Aphis urticata, Dasineura urticata, Tritomegas sexmaculatus. Inachis io has been the only species which during the observation period did danger the stinging nettle stand. The other pest species have not threated even timely either the stinging nettle stand or a single plant. The number and diversity of natural enemies was rather low: running crab spiders (Philodromidae), tangle-web spiders (Theridiidae), crabbing spiders (Thomisidae), lacewings (Chrysopa perla, Chrysopa formosa), coccinellids (Coccinella septempunctata, Propylea quattuordecimpunctata, Adonia variegata), hoverflies (Episyrphus balteatus), earwigs (Forficula auricularia), scorpionflies (common scorpionfly (Panorpa communis) and European paper wasp (Polistes dominula) predominated.